In vitro, in silico and in vivo study challenges the impact of bronchial thermoplasty on acute airway smooth muscle mass loss - Chernyavsky, Igor L.; Russell, Richard J.; Saunders, Ruth M.; Morris, Gavin E.; Berair, Rachid; Singapuri, Amisha; Chachi, Latifa; Mansur, Adel H.; Howarth, Peter H.; Dennison, Paddy; Chaudhuri, Rekha; Bicknell, Stephen; et al. (European Respiratory Society, 2018)
Bronchial thermoplasty is a treatment for asthma. Whether during thermoplasty the airway wall fraction exposed to temperatures necessary to affect cells is sufficient to explain its histopathological impact is unclear. Airway smooth muscle and bronchial epithelial cells were exposed to media (37-70°C) for 10 seconds to mimic thermoplasty. In silico we developed a mathematical model of airway heat distribution following thermoplasty. In vivo we determined airway smooth muscle mass and epithelial integrity pre- and post-thermoplasty in 14 severe asthmatics. In vitro airway smooth muscle and epithelial cell number decreased significantly following addition of media heated to ≥65°C. In silico simulations showed heterogeneous heat distribution; amplified in larger airways, with <10% of the airway wall heated >60°C for airways with an inner radius ~4mm. In vivo 6 weeks post-thermoplasty asthma control (ACQ6) improved (mean difference: 0.7 [95%-CI 0.1-1.3]; p=0.03), airway smooth muscle mass decreased (absolute median reduction: 5 [IQR 0-10]%; p=0.03) and epithelial integrity increased (14 [6-29]%; p=0.007); neither of which were related to improved asthma control. Integrated in vitro and in silico modelling suggested that the reduction in airway smooth muscle post-thermoplasty cannot be fully explained by acute heating; nor did this reduction confer a greater improvement in asthma control.